Principle-Based Stepped Care and Brief Psychotherapy for Integrated Care Settings 2018
DOI: 10.1007/978-3-319-70539-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease

Abstract: Background: A study was undertaken to test the hypothesis that patients respond better to lung volume reduction surgery (LVRS) if their emphysema is confluent and predominantly located in the upper lobes. Methods: A density mask analysis was used to identify voxels inflated beyond 10.2 ml gas/g tissue (-910 HU) on preoperative and postoperative CT scans from patients receiving LVRS. These hyperinflated regions were considered to represent emphysematous lesions. A power law analysis was used to determine the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Higher rates of COPD were traditionally found among a male population; however, recent research has identified that females are at a greater risk for COPD [ 34 , 35 ]. Several studies have indicated that lower socioeconomic status, including income and education level, serves as a predictive factor for COPD [ 36 - 38 ]. These characteristics are linked to poor health status in the general population within the literature [ 37 ].…”
Section: Copd and Mental Healthmentioning
confidence: 99%
“…Higher rates of COPD were traditionally found among a male population; however, recent research has identified that females are at a greater risk for COPD [ 34 , 35 ]. Several studies have indicated that lower socioeconomic status, including income and education level, serves as a predictive factor for COPD [ 36 - 38 ]. These characteristics are linked to poor health status in the general population within the literature [ 37 ].…”
Section: Copd and Mental Healthmentioning
confidence: 99%